The comparison of quality of life of female patients over and below 41 years of age with lower limbs ulcerataion treated surgically or conservatively - Makara-Studzińska, Marta; Podstawka, Danuta; Wilczek, Małgorzata; Kryś-Noszczyk, Karolina (Current Problems of Psychiatry, 2012)
Crural ulcerations are associated with age and are much more common in people over 60 years of age. Ulcers etiologic factors include: genetic predisposition, factors related to the conditions and lifestyle. Often they are the result of co-morbidities such as arterial disease, diabetes, or rheumatoid arthritis. Ulcerating changes cause physical discomfort, mental depression, which contributes to social isolation. Research indicates that with increasing age, health becomes the primary and one of the main determinants of the quality of life. Complications occurring in the elderly connected with ulcers, and venous insufficiency lead to lower quality of life. The study group comprised patients with leg ulcers treated in the Military Hospital with Policlinic in the Public Health Institute, Al. Racławickie 23 in Lublin in the Department of Surgery. The group size was 60 patients. To assess the quality of life of patients with leg ulcers a shortened version of the questionnaire WHOQOL - BREF w as u sed i n assessing the quality of life. This survey consists of 26 questions, which describe the quality of life in four areas: physical, psychological, social and environmental. The study also used a brief authors’ questionnaire. The research confirms that the age of patients with leg ulcers differentiates their assessment of the quality of life. In the group of patients over 41 years of age the quality of life was assessed lower; primarily it concerned somatic, psychological and environmental areas. The age of patients significantly influenced the assessment of the quality of their lives.